Fully automated assessment of the severity of Parkinson's disease from speech. (January 2015) - Bayestehtashk, Alireza; Asgari, Meysam; Shafran, Izhak; McNames, James
Abstract : Highlights: Development of better models for extraction of features related to pitch, jitter and shimmer. Analysis of the effectiveness of different tasks for eliciting speech. Demonstration of the feasibility of administering a battery of PD tests on a portable platform and automating the analysis of elicited speech. Abstract: For several decades now, there has been sporadic interest in automatically characterizing the speech impairment due to Parkinson's disease (PD). Most early studies were confined to quantifying a few speech features that were easy to compute. More recent studies have adopted a machine learning approach where a large number of potential features are extracted and the models are learned automatically from the data. In the same vein, here we characterize the disease using a relatively large cohort of 168 subjects, collected from multiple (three) clinics. We elicited speech using three tasks – the sustained phonation task, the diadochokinetic task and a reading task, all within a time budget of 4 min, prompted by a portable device. From these recordings, we extracted 1582 features for each subject using openSMILE, a standard feature extraction tool. We compared the effectiveness of three strategies for learning a regularized regression and find that ridge regression performs better than lasso and support vector regression for our task. We refine the feature extraction to capture pitch-related cues, including jitter and shimmer, more accurately using a time-varying harmonic model of speech. Our results show that the severity of the disease can be inferred from speech with a mean absolute error of about 5.5, explaining 61% of the variance and consistently well-above chance across all clinics. Of the three speech elicitation tasks, we find that the reading task is significantly better at capturing cues than diadochokinetic or sustained phonation task. In all, we have demonstrated that the data collection and inference can be fully automated, and the results show that speech-based assessment has promising practical application in PD. The techniques reported here are more widely applicable to other paralinguistic tasks in clinical domain.